1979
DOI: 10.1080/00222347908215183
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties of α-keratin fibers during extension

Abstract: Lincoln wool fibers have been tested for their dynamic modulus E' and loss angle 6 at various values of strain in the "Hookean", yield, and postyield regions by applying various rates of extension, and in atmospheres varying from 0 to 100% relative humidity. An estimate of the energy loss per cycle for the whole fiber exhibits only minor change over the complete range of change of the humidity and strain. The dynamic modulus E' and loss angle 6 change considerably with overall strain of the fiber, especially u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The relaxation of the wool fiber in water is different in nature from the relaxation in the alcohols or at lower relative humidities [14,16], as was shown by Danilatos [19] in dynamic mechanical experiments on wool fibers in water. Danilatos observed that even at high frequencies, equivalent to short relaxation times, no upper plateau value for the modulus is reached and that the part of the relaxation curve experimentally accessible spans considerably more than the expected nine decades of time.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The relaxation of the wool fiber in water is different in nature from the relaxation in the alcohols or at lower relative humidities [14,16], as was shown by Danilatos [19] in dynamic mechanical experiments on wool fibers in water. Danilatos observed that even at high frequencies, equivalent to short relaxation times, no upper plateau value for the modulus is reached and that the part of the relaxation curve experimentally accessible spans considerably more than the expected nine decades of time.…”
Section: Discussionmentioning
confidence: 93%
“…Various investigations have shown the applicability of the log-normal distribution in its integral form [2,15,16,19] to describe the relaxation function under various environmental and experimental conditions, yielding for the ln-time scale:…”
Section: Discussionmentioning
confidence: 99%
“…Because of this consideratiun, the theoretical stiffness of the a-helix can be doubled. Druhala [11] ] used an effective cross-sectional area of the a-helix calculated from the known crosssectional area of the microfibril and arrived at a figure of about 2 nm2, but an average cross-sectional area of about 1 nM2 for the a-helix is preferable [23]. Consequently the theoretical value for the modulus of the a-helix can be further doubled.…”
Section: Consequentlymentioning
confidence: 99%
“…In order to compare the dynamic measurements with those obtained by relaxation techniques, the transformation of frequency to time was obtained using the method of Ninomiya and Ferry12: components of the complex modulus with magnitude E a t time t. In practice it was found that E ( t ) N E'(~)l,=i/t (2) Using the relation ( 2 ) , Mason's result is shown in Figure 1 together with those of Chaikin and Chamberlain for three relative humidities. Comparing these points, it seems that there must be an abrupt decrease of modulus from the value a t 100 kHz and 65% RH to the value at 20 kHz and 100% RH.…”
Section: The Tensile Modulus Of Keratin Fibers As a Function Of Timementioning
confidence: 99%